HANNAH BAKER’S SUICIDE AS SEEN IN JAY ASHER’S THIRTEEN REASONS WHY - Pujimahanani, Cahyaningsih; Firdaus, Mochammad Haqqi (Dinamika : Jurnal Sastra dan Budaya, 2018)
This thesis focuses on Hannah Baker?s suicide in Jay Asher?s Thirteen Reasons Why. The objectives of the study are to find out the proof Hannah Baker?s suicide in the novel, the causes of Hannah Baker?s suicide, and the effects of Hannah Baker?s suicide to their parents and friends as seen in Jay Asher?s Thirteen Reasons Why. Thesis writer also applies qualitative approach and the theory used is suicide theory. The finding shows that Hannah Baker commits suicide. She uses pills as the means of her suicide. The causes of Hannah Baker?s suicide is caused by three factors as she stated. Those are hurt, anguish, soreness and aching. The effects of Hannah Baker?s suicide to her parents and friends are that Hannah makes her parents in a dysfunctional states. They are mourning for her and abandon everything and move back to the old city. Hannah?s suicide also causes blaming issues for her friends. It shows that her friends blame each other and Hannah, in addition, one of her friends has self-blame issues. Also, it makes them being perceived more negative by other characters.Key words: Suicide